Rhetorical Analysis of David Čеrný’s Art Installation “Entropa: Stereotypes and Barriers to Be Demolished” - Yordanova, Rossitza (Media and Language, 2020)
The aim of the rhetorical analysis of  David Černý’s art installation “Entropa: stereotypes and barriers to be demolished” is to answer the following the questions: What is the rhetorical situation? What is the audience it addresses? Who is the author? What is the purpose of the visual rhetorical message? In what genre can the art installation be placed? What visual images and visual argumentation are used to achieve the purpose? What is the effect and how did the audience respond to Černý’s installation? The specific interdisciplinary scientific field of the relation between rhetoric and neoavantgarde art is the background against which we analyze the creation as well as the setting in which the art installation is perceived and interpreted as visual political rhetorics.
Keywords: David Černý; installation; rhetoric – neoavantgarde art; stereotypes and biases in intercultural communication; visual rhetorical images